2022
DOI: 10.1002/eap.2690
|View full text |Cite
|
Sign up to set email alerts
|

The role of microtopography and resident species in post‐disturbance recovery of arid habitats in Hawaiʻi

Abstract: Habitat-suitability indices (HSI) have been employed in restoration to identify optimal sites for planting native species. Often, HSI are based on abiotic variables and do not include biotic interactions, even though similar abiotic conditions can favor both native and nonnative species. Biotic interactions such as competition may be especially important in invader-dominated habitats because invasive species often have fast growth rates and can exploit resources quickly. In this study, we test the utility of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Previous work in Hawaiian dry forests has shown that sites that are favorable to native species also tend to favor an abundance of invasive grasses (Questad et al, 2012), but due to the lower growth rates of native species, invasive grasses remain persistent or take over sites over time (Yelenik, Rose, Cordell, et al, 2022). Native grass E. atropioides also showed significant declines within disturbed relative to control plots, with some increases in bare ground and B. catharticus, suggesting a slight shift in species composition.…”
Section: Amosaicofinvasivedominationwith Persistent Native Speciesmentioning
confidence: 88%
See 3 more Smart Citations
“…Previous work in Hawaiian dry forests has shown that sites that are favorable to native species also tend to favor an abundance of invasive grasses (Questad et al, 2012), but due to the lower growth rates of native species, invasive grasses remain persistent or take over sites over time (Yelenik, Rose, Cordell, et al, 2022). Native grass E. atropioides also showed significant declines within disturbed relative to control plots, with some increases in bare ground and B. catharticus, suggesting a slight shift in species composition.…”
Section: Amosaicofinvasivedominationwith Persistent Native Speciesmentioning
confidence: 88%
“…This variation in colonizer versus competitor syndrome occurred both between species and also within species among different habitats. This points to the importance of resident communities and their effects on species interactions in shaping a plant community's response to disturbance (Hulvey & Aigner, 2014 ; Yelenik, Rose, Cordell, et al., 2022 ). These results are also likely driven by seed availability, or, in the case of C. clandestinus , rhizome availability (HilleRisLambers et al., 2010 ; Hulvey & Aigner, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the relationships between species and specific biophysical variables can be used to predict sites where planting or translocation efforts will be most successful based on microhabitat (Questad et al 2014). These techniques for threatened and endangered species, however, rarely incorporate biotic interactions, such as competition from invasive species, potentially leading to spurious conclusions about how species shift given climate change (Alexander et al 2015) or altering the utility of habitat suitability models (Yelenik et al 2022).…”
Section: Introductionmentioning
confidence: 99%